2022
DOI: 10.2320/matertrans.mt-y2021005
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Characterization and Computational Simulation of Powder Bed for Powder Bed Fusion Additive Manufacturing

Abstract: The packing density of powder bed is one of the critical parameters affecting the quality of the final parts fabricated via powder bed fusion additive manufacturing. In this study the packing density of the first layer of the powder bed was experimentally estimated from the packing densities of recoated powder with different number of layers. It is found that the packing density of the first layer is much lower than the apparent density of powder and the macro-scale packing density increases as the number of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…This suggests the importance of powder bed properties in the melting and solidification phenomena in the L-PBF process. While this study focused on the average particle diameter, some previous studies using DEM simulation have suggested that powder particle shape, as well as the shape and travelling speed of the coater blade, can also affect powder bed properties [35,37,52,[58][59][60].…”
Section: Molten Pool Dimensionsmentioning
confidence: 99%
“…This suggests the importance of powder bed properties in the melting and solidification phenomena in the L-PBF process. While this study focused on the average particle diameter, some previous studies using DEM simulation have suggested that powder particle shape, as well as the shape and travelling speed of the coater blade, can also affect powder bed properties [35,37,52,[58][59][60].…”
Section: Molten Pool Dimensionsmentioning
confidence: 99%